Development Ways of the Idea of Forming Ecological Culture among Students of the Republic of Karakalpagistan - Imametdinovich, Khusnetdinov Ulugbek (International Journal on Integrated Education, 2023)
In the article, the trends of eco–enlightenment in higher educational institutions in the Republic of Karakalpakstan. Based on the ethno–ecological traditions of the Karakalpaks, the chronology of the development of ecological enlightenment and culture and the main trends of the mythological views on ecological education in the earliest times are highlighted.